Thrombin-Induced Platelet Secretion: FURTHER EVIDENCE FOR A SPECIFIC PATHWAY - Shuman, M. A. (1979)
We have studied the interaction between thrombin and washed, human platelets using prostacyclin, a reversible inhibitor of platelet secretion. The effect of thrombin is limited to those reactions that are not inhibited by an increased concentration of platelet cyclic adenosine 3′,5′-monophosphate, because prostacyclin is a potent inducer of the latter. Prostacyclin-treated platelets were briefly (15-30 s) exposed to low concentrations of human thrombin (0.01-0.2 U/ml). After removal of the prostacyclin and thrombin, the platelets were incubated with fresh thrombin. Although they had not undergone the release reaction after the first thrombin incubation, these platelets had a diminished capacity to secrete [(3)H]serotonin when exposed to thrombin the second time. Refractoriness was concentration dependent: the higher the initial thrombin concentration, the greater the degree of inhibition of serotonin secretion on subsequent thrombin exposure. Inhibition was closely related to the ability of thrombin to induce platelet secretion and not to its esterase or fibrinogen clotting activity. Diisopropyl fluorophosphate-inactive thrombin did not induce refractoriness. Refractoriness to thrombin did not increase when the time of the initial incubation with thrombin was lengthened, nor was it reversible. Inhibition was thrombin specific: serotonin secretion induced by collagen, wheat germ agglutinin, and the ionophore A23187 was minimally affected. For an equivalent amount of thrombin bound, a decrease was observed in serotonin secretion by thrombin-pretreated platelets compared to control platelets. Thus, there is at least one step in the secretory pathway between thrombin binding and regulation of adenylate cyclase. This step appears to transmit the signal that leads to extrusion of intracellular granular contents.